Sustainable blends of LDPE/NR and sugarcane bagasse ashes with PE-g-MA thermomechanical relationships - Torre, Giovanni Barrera; Dognani, Guilherme; Cabrera, Flávio Camargo; Alzate, Júlio Cézar; Souza, José Alexandrino De; Reis, Elton Prado Dos; Teixeira, Silvio Rainho; Job, Aldo Eloizo (Rede Latino-Americana de Materiais, 2019)
ABSTRACT The polymer blends obtained with residues that before were called wastes has been growing as a viable solution, allowing improvements in the mechanical properties and as sustainable alternative. This work reports the effects of blends of low-density polyethylene (LDPE) and natural rubber (NR), with sugar cane bagasse ash (SCBA) as filler, with and without polyethylene-graft-maleic anhydride (PE-g-MA) how coupling agent. The dynamic mechanical behavior and a stress-strain analysis were studied. The materials were further evaluated by differential scanning calorimetry and morphological observations. The results showed that incorporation of the PE-g-MA reduced the strain and improved the stress and the Young module of the mixtures. Moreover, the presence of SCBA increased the hardness while maintaining the tensile strength and the elongation behavior of the polymer. The results demonstrate the potential use of SCBA in the elastomer and thermoplastic mixture, free of vulcanization agents.

RESUMO As blendas poliméricas obtidas com resíduos que antes eram chamados de lixos vêm crescendo como uma solução viável, permitindo melhorias nas propriedades mecânicas e como alternativas sustentáveis. Este trabalho relata os efeitos de misturas de polietileno de baixa densidade (PEBD) e borracha natural(NR), com cinzas de bagaço de cana-de-açúcar (CBCA) como carga, com e sem polietileno-enxertado com anidrido maleico (PE-g-MA) como agente de ligação. Os comportamentos dinâmico-mecânico e a análise de tensão-deformação foram estudados. Os materiais foram avaliados por calorimetria diferencial de varredura e observações morfológicas. Os resultados mostraram que a incorporação do PE-g-MA reduziu a deformação e melhorou o estresse e o módulo Young das misturas. Além disso, a presença de SCBA aumentou a dureza, mantendo a resistência à tração e o comportamento de alongamento do polímero. Os resultados demonstram o potencial uso da CBCA na mistura de elastômeros e termoplásticos, livres de agentes de vulcanização.
Misturas sosteniveis de PEBD/BN e cinzas de bagaço da cana de açúcar Com PE-g-AM relações termomecânicas
Keywords: Sustainable blends; sugarcane bagasse ashes; natural rubber; low density polyethylene; polyethylene-graft-maleic anhydride; Misturas sustentáveis; cinzas de bagaço de cana-de-açúcar; borracha natural; polietileno de baixa densidade; polietileno-enxertado com anidrido maleico